Role of Pre-operative Inflammatory Markers as Predictors of Lymph Node Positivity and Disease Recurrence in Well-Differentiated Pancreatic Neuroendocrine Tumours: Pancreas2000 Research and Educational Program (Course 9) - Tanno, Lulu; Pea, Antonio; Nykänen, Taina; Prasad, Pooja; Tuncer, Ceren; Marchegiani, Giovanni; Robinson, Stuart (Frontiers in Medicine, 2020)
Pancreatic neuroendocrine tumours (PNET) is a rare disease and in the absence of metastases, surgical resection is recommended. Key factors affecting survival in PNETs are the stage and grade of the disease, but there is increasing evidence suggesting lymph node involvement is associated with shorter disease-free and overall survival. Ability to predict the likelihood of lymph node involvement at the time of diagnosis would affect surgical decision making in these patients. A systemic inflammatory index such as neutrophil to lymphocyte ratio or platelet to lymphocyte ratio has been associated with poor prognosis in several cancers. Method: This study is a retrospective multi-centre study. The data including pre-operative inflammatory markers such as haemoglobin, neutrophil, lymphocyte counts and pathological data including number of positive lymph nodes, tumour grade and size, are collected to assess the association between inflammatory index and lymph node involvement. conclusion: This study aims to assess the value of routinely available pre-operative haematological markers in predicting lymph node involvement in non-functioning PNETs. Integrated research application number (IRAS) 268529